Contesting British Chinese Culture (Springer International Publishing, 2018)
This is the first text to address British Chinese culture. It explores British Chinese cultural politics in terms of national and international debates on the Chinese diaspora, race, multiculture, identity and belonging, and transnational 'Chineseness'. Collectively, the essays look at how notions of 'British Chinese culture' have been constructed and challenged in the visual arts, theatre and performance, and film, since the mid-1980s. They contest British Chinese invisibility, showing how practice is not only heterogeneous, but is forged through shifting historical and political contexts; continued racialization, the currency of Orientalist stereotypes and the possibility of their subversion; the policies of institutions and their funding strategies; and dynamic relationships with transnationalisms. The book brings a fresh perspective that makes both an empirical and theoretical contribution to the study of race and cultural production, whilst critically interrogating the very notion of British Chineseness.